Designing for exploratory play with a hackable digital musical instrument - McPherson, Andrew P.; Chamberlain, Alan; Hazzard, Adrian; McGrath, Sean; Benford, Steve (ACM, 2016)
This paper explores the design of digital musical instruments (DMIs) for exploratory play. Based on Gaver’s principles of ludic design, we examine the ways in which people come to terms with an unfamiliar musical interface. We describe two workshops with the D-Box, a DMI designed to be modified and hacked by the user. The operation of the D-Box is de- liberately left ambiguous to encourage users to develop their own meanings and interaction techniques. During the work- shops we observed emergent patterns of exploration which re- vealed a rich process of exploratory play. We discuss our ob- servations in relation to previous literature on appropriation, ambiguity and ludic engagement, and we provide recommen- dations for the design of playful and exploratory interfaces.